PHOTOELECTROCHEMISTRY OF COPPER OXIDES ANODICALLY FORMED ON Cu–Zn ALLOYS - Nesterova Marija Yu. (Конденсированные среды и межфазные границы, 2017)
This paper is aimed at revealing the infl uence of the vacancy defectiveness of the Cu–Zn alloys surface layer on the kinetics of oxide formation and structure-sensitive properties of thin oxide fi lms. Selective dissolution is used to generate superequilibrium vacancies in the alloys surface layer. Preliminary selective dissolution with a monitored potential, charge, and concentration of vacancies was carried out in deoxygenated 0.01 M HCl + 0.09 M KCl. Subsequent anodic oxidation of Cu–Zn alloys was carried out in deoxygenated 0.1 M KOH at the potentials of formation of Cu(I) and Cu(II) oxides. Chronoamperometry with synchronous registration of photocurrent and photopotential measurements in the open circuit were applied. The kinetics of anodic oxide formation is solid phase diffusion. The effective diffusion coeffi cient slightly increases with the potential of oxide formation and zinc concentration in the alloy. It was established p-type conductivity for Cu(I) and Cu(II) oxides on Cu–Zn alloys caused by prevalence of acceptor defects. Cathodic photocurrent increases in the course of polarization, refl ecting the thickening of oxide fi lm. Positive photopotential increases over time after polarization is switched off, indicating the corrosion oxidation of copper from oxide-free electrode surface. The dependence of photocurrent and photopotential over time proves that the thickness of oxide fi lms is less than the space charge region. Quantitative processing of photocurrent vs. fi lm thickness curves provides a set of structural-sensitive parameters, among which the light absorption coeffi cient α, the concentration of acceptor defects NA, space charge region W and Debye length LD. Preliminary selective dissolution as well as the growth of zinc concentration in Cu–Zn alloys results in an increase of α and NA supplied with a decrease of W and LD.